Plaques depicting various types of flora, fauna and hybrid creatures - Temples of India Project Team (Jio Institute, 2024)
Tablet-like plaques are placed on the adhisthana (east). The plaques have depictions of various types of flora and fauna and hybrid creatures like kinnara, vyala, and makara. The plaques are tightly arranged, richly detailed, and deeply carved, creating contrasting shadows that make the artwork look three-dimensional in sunlight. The central artwork of the plaque is in the form of a circular medallion surrounded by a foliage motif. The left plaque features simha (lion) vyala and gaja (elephant) vyala engaged in a fight. The right plaque features a stylised makara. The plaques are separated by squat pillars which have a square base, an octagonal shaft, and a square capital. The pillars are decorated with ardha padma (half lotus) and kalpa lata (creeper) motifs.